1962
DOI: 10.1161/01.res.11.2.240
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blood Flow and Left Atrial Pressure on Pulmonary Venous Resistance

Abstract: Pulmonary venular pressure was measured in 11 thoracotomized dogs and in 8 isolated lung lobes by introducing a small catheter (O.D. 0.6 or 0.9 mm.) as far as possible retrograde into the pulmonary veins. In thoracotomized dogs, insufflated with a maximal air pressure of 6 mm. Hg, the mean pulmonary arterial, venular, and left atrial pressures averaged 18.4, 9.1, and 4.2 mm. Hg, respectively. An almost linear relationship was found between venular pressure and pulmonary blood flow, except in the low flow range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1966
1966
2005
2005

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The latter effect is of importance since wide fluctuations in left atrial pressure can strongly influence calculated pulmonary resistance independent of neural effects on vessel caliber (17,22,23). However, enhanced vascular resistance together with elevated mean arterial pressure and essentially unchanged mean left atrial pressure during left stellate ganglion stimulation is a strong indication of vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…The latter effect is of importance since wide fluctuations in left atrial pressure can strongly influence calculated pulmonary resistance independent of neural effects on vessel caliber (17,22,23). However, enhanced vascular resistance together with elevated mean arterial pressure and essentially unchanged mean left atrial pressure during left stellate ganglion stimulation is a strong indication of vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…This concept is supported by radiographic (Kjellberg and Olsson, 1954) and experimental (Little, 1960) observations. The contribution in the regulation of the pulmonary venous pressure and blood flow has also been attributed to the sleeves ensheathing the veins in physiological and experimental conditions (Eliakim and Aviado, 1961;Kuramoto andRodbard, 1962, Smith andCoxe, 1951;Gilbert, Hinshaw, Kuida, and Visscher, 1958;Rudolph, Gootman, Golinko, and Scarpelli, 1961). Descriptions of active expulsion of blood from the veins into the atria, facilitating the filling of the atria, have also appeared in the literature (Carrow and Calhoun, 1964).…”
Section: Discussionmentioning
confidence: 99%
“…Thus in the adult lung, because the pulmonary veins are thin walled and sparsely innervated, they act mainly as conduit vessels to drain oxygenated blood into the left ventricle (32,85). However, other investigators, from measurement of venular pressures using small catheters, have found that a substantial portion of the total pulmonary vascular resistance is in veins (75,92,147). Similarly, from detailed morphometric measurements of cat lung, 49% of the total vascular resistance was calculated to be in veins, which the authors attributed to the branching pattern of the veins and the viscoelastic properties of the vessel walls (169).…”
Section: Contribution Of Veins To Total Pulmonary Vascular Resistancementioning
confidence: 99%